Adaptive second order terminal sliding mode controller for robotic manipulators - Mondal, Sanjoy; Mahanta, Chitralekha (Journal of the Franklin Institute, 2014)
In this paper an adaptive second order terminal sliding mode (SOTSM) controller is proposed for controlling robotic manipulators. Instead of the normal control input, its time derivative is used in the proposed controller. The discontinuous sign function is contained in the derivative control and the actual control obtained after integration is continuous and hence chatterless. An adaptive tuning method is utilized to deal with the system uncertainties whose upper bounds are not required to be known in advance. The performance of the proposed control strategy is evaluated through the control of a two-link rigid robotic manipulator. Simulation results demonstrate the effectiveness of the proposed control method. •An adaptive second order terminal sliding mode controller is designed for a two link robotic manipulator.•The adaptive tuning law implemented in the proposed controller eliminates the need for any prior knowledge about the uncertainty bound of the robotic manipulator.•The actual control signal obtained by integrating the derivative control signal is smooth and chattering free.•The proposed control law results in lesser total variation in the control input and requires lesser control energy.